2009
DOI: 10.1093/europace/eup038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 'super-responders' to cardiac resynchronization therapy: the importance of symptom duration and left ventricular geometry

Abstract: Patients in earlier phases of the cardiomyopathy, with a less altered ventricular geometry, seem to have a greater probability of becoming super-responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 12 publications
9
53
0
8
Order By: Relevance
“…In a study by Anthony et al 15 , patients in the earliest stages of cardiomyopathy and minor alterations in ventricular geometry were more likely to respond to CRT. Additionally, the evaluation of volumetric changes after CRT provides important predictive information about the clinical outcomes in the natural evolution of the disease, as demonstrated originally by Yu et al 16 and confirmed in a recent study by Ypenburg et al 17 .…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Anthony et al 15 , patients in the earliest stages of cardiomyopathy and minor alterations in ventricular geometry were more likely to respond to CRT. Additionally, the evaluation of volumetric changes after CRT provides important predictive information about the clinical outcomes in the natural evolution of the disease, as demonstrated originally by Yu et al 16 and confirmed in a recent study by Ypenburg et al 17 .…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study corroborate that of others who also demonstrated hyper-responsive patterns in patients with less advanced heart disease. 5,6,12 In the MADIT-CRT (Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy) study, in patients with mild symptoms of heart failure, the female gender, absence of infarction, LBBB, QRS > 150 ms, BMI < 30 kg/m 2 and reduced left atrial volume were predictors of SR. 8 Our study included a group of patients with very symptomatic CHF, with 64% of patients having been previously hospitalized for recently decompensated CHF. These differences in the population characteristics may explain some differences in the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Some authors have described groups of patients that progressed with higher responses than the expected ones, with normalization of left ventricular function, FC, and ventricular diameters, thus being called hyperresponders or Super-Responders (SR), ranging from 9 to 21% in several studies. [4][5][6] The characteristics of these patients have been assessed, and the super-response is interpreted as a possible cardiomyopathy induced by cardiac dyssynchrony, caused by the intra-ventricular conduction disorder. 7 Predictors of super-response are the female gender, non-ischemic heart disease (Chagas cardiomyopathy not included) and Left Bundle-Branch Block (LBBB).…”
Section: Introductionmentioning
confidence: 99%
“…В более поздних работах авторы также использовали динамику ФВ ЛЖ, как критерий «суперответа», однако целевой уровень ФВ ЛЖ менял-ся от исследования к исследованию [17][18][19]. До сих пор нет единого мнения о том, какого критерия следует при-держиваться при определении понятия «суперреспон-дер» [20][21][22][23]. В нашем исследовании, как и в ряде других крупных исследований, пациенты были отнесены в груп-пу «суперреспондеров», если через 6 мес после имплан-тации снижение КСО ЛЖ составило 30 % и более [16,24,25].…”
Section: Discussionunclassified